Patient and professional user experiences of simple telehealth for hypertension, medication reminders and smoking cessation: a service evaluation. Issue 3 (20th March 2015) - Cottrell, Elizabeth; Cox, Tracey; O'Connell, Phil; Chambers, Ruth
Abstract : Objectives: To establish patient and professional user satisfaction with the Advice & Interactive Messaging (AIM) for Health programme delivered using a mobile phone-based, simple telehealth intervention, 'Florence'. Design: A service evaluation using data extracted from Florence and from a professional user electronic survey. Setting: 425 primary care practices across 31 Clinical Commissioning Groups in England. Participants: 3381 patients registered on 1 of 10 AIM protocols between March 2013 and January 2014 and 77 professional users. Intervention: The AIM programme offered 10 clinical protocols, in three broad groups: (1) hypertension diagnosis/monitoring, (2) medication reminders and (3) smoking cessation. Florence sent patients prompts to submit clinical information, educational messages and user satisfaction questions. Patient responses were reviewed by their primary healthcare providers. Primary outcome measures: Patients and professional user experiences of using AIM, and within this, Florence. Results: Patient activity using Florence was generally good at month 1 for the hypertension protocols (71–80%), but reduced over 2–3 months (31–60%). For the other protocols, patient activity was 0–39% at 3 months. Minimum target days of texting were met for half the hypertension protocols. 1707/2304 (74%) patients sent evaluative texts responded at least once. Among responders, agreement with the adapted friends and family statement generally exceeded preproject aspirations. Professional responders were generally positive or equivocal about the programme. Conclusions: Satisfaction with AIM appeared optimal when patients were carefully selected for the protocol; professional users were familiar with the system, the programme addressed a problem with the previous service delivery that was identified by users and users took an active approach to achieve clinical goals. However, there was a significant decrease in patients' use of Florence over time. Future applications may be optimised by identifying and addressing reasons for the waning use of the service and enhancing support during implementation of the service.